New Teachers’ Career Intentions: Factors Influencing New Teachers’ Decisions to Stay or to Leave the Profession - Fontaine, Sylvie; Kane, Ruth; Duquette, Olivier; Savoie-Zajc, Lorraine (Alberta Journal of Educational Research, 2012)
This study examines the relationship between the reported career intentions and perceptions of preparedness of graduating secondary teachers in Quebec, across a two- year period, in an effort to identify factors which contribute to growing attrition rates among beginning teachers. The study reveals that those beginning teachers most concerned with their lack of preparation in the areas of classroom management and assessment of students’ learning are more likely to consider leaving the profession. While evidence suggests that beginning teachers do develop increasing confidence in terms of classroom management in their second year of teaching, their challenges with effectively assessing student learning endure through the first two years of teaching. Findings from this mixed method study suggest that both initial teacher education and employers have a shared responsibility to give greater attention to the ways in which teachers are introduced to and have experience with strategies for the assessment of student learning. Cette étude porte sur le rapport entre les intentions de carrière et les perceptions qu’ont les finissants en enseignement secondaire au Québec quant à leur niveau de préparation. La recherche s’est étalée sur deux ans et visait à identifier les facteurs qui contribuent au taux grandissant d’attrition chez les enseignants débutants. L’étude a révélé que les enseignants débutants qui sont les plus préoccupés par leur manque de préparation en matière de gestion de classe et en évaluation des apprentissages sont également susceptibles de penser à quitter la profession. Bien que les résultats montrent que les enseignants débutants tendent à devenir plus confiants en gestion de classe pendant leur deuxième année d’enseignement, leur défis quant à l’évaluation des apprentissages persistent tout au long de leur deuxième année d’enseignement. Les résultats de cette étude qui reposent sur une méthode mixte indiquent également que, tant la formation initiale des enseignants que les employeurs, doivent porter attention à la présentation des notions relatives à l’évaluation des apprentissages et aux expériences qui sont offertes aux enseignants en début de carrière.